2004
DOI: 10.1093/annonc/mdh100
|View full text |Cite
|
Sign up to set email alerts
|

Continuously infused carboplatin used as radiosensitizer in locally unresectable non-small-cell lung cancer: a multicenter phase III study

Abstract: Addition of continuously administered carboplatin as radiosensitizer for locally unresectable NSCLC does not improve local tumor control or overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…However, although uninterrupted CRT to full doses of 60 Gy or higher can avoid treatment gaps, a radical resection was only achieved in 28% of these carefully selected patients, with a pathological complete response in 30% of the latter. It should, however, be noted that these authors evaluated carboplatin combinations concurrent with chemotherapy, even though carboplatin as a single agent has not been shown in the previous trials to improve local control over that achieved using only radiotherapy [20,21]. The pattern of distant relapses, especially brain metastases, following CRT is also a topic of studies evaluating prophylactic cranial irradiation in this setting [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…However, although uninterrupted CRT to full doses of 60 Gy or higher can avoid treatment gaps, a radical resection was only achieved in 28% of these carefully selected patients, with a pathological complete response in 30% of the latter. It should, however, be noted that these authors evaluated carboplatin combinations concurrent with chemotherapy, even though carboplatin as a single agent has not been shown in the previous trials to improve local control over that achieved using only radiotherapy [20,21]. The pattern of distant relapses, especially brain metastases, following CRT is also a topic of studies evaluating prophylactic cranial irradiation in this setting [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that better local control of lung cancer can lead to an improvement in overall survival, prompting interest in altering radiotherapy delivery regimes [3]. In addition to the less toxic alternative of sequential chemo-radiotherapy, radiotherapy dose escalation has been explored, given conventional doses achieve sub-optimal rates of local disease control with estimates of pathologically persistent tumour following treatment in 60% of patients [41]. Indeed, one of the strategies to improve local control is dose escalation.…”
Section: Chemoradiotherapy Paradigm In Stage III Nsclc: What Is the Bmentioning
confidence: 99%
“…Better survival was found in patients with NSCLC presenting with an objective response to induction chemotherapy before surgery or to treatment for locoregionally advanced NSCLC, induction chemotherapy before radiotherapy, chemoradiotherapy, or radiotherapy alone [59][60][61][62][63][64]. The level of evidence was from analyses of secondary objectives of randomised trials published on each topic (table 6) and phase II studies [66][67][68][69][70][71][72][73][74].…”
Section: Question 1: Can the Criteria Of Pfs Ttp And Dfs Be Used To mentioning
confidence: 99%